COMPARATIVE STUDY OF BLOOD GLUCOSE LEVELS AND THE DEGREE OF LIVER AND KIDNEY DAMAGE IN DIABETIC ANIMAL MODELS INDUCED BY ALLOXAN, STREPTOZOTOCIN, AND STREPTOZOTOCIN-NICOTINAMIDE - Miswari, Irna; Husna, Fauzul; Zulkarnain, Zulkarnain; Syahrizal, Dedy; Syahputra, Andika Ari; Hasan, Denny Irmawati (Jurnal Kedokteran Hewan, 2025)
The objective of this study was to assess differences in body weight, blood glucose levels, and liver and kidney tissue damage among rats induced with alloxan, streptozotocin, or streptozotocin-nicotinamide. This was an experimental study using a completely randomized design. The rats were allocated into four experimental groups. Group 1 (KN) was considered as the normal control group, while groups K1, K2, and K3 were induced with streptozotocin (60 mg/kg bw), alloxan (150 mg/kg bw), and nicotinamide (120 mg/kg bw) followed by streptozotocin (60 mg/kg bw), respectively. The compounds were administered intraperitoneally using suitable solvents. Body weight and blood glucose levels were monitored weekly. Upon completion of the study, liver and kidney tissues were harvested and processed for histopathological analysis using hematoxylin-eosin staining. The findings revealed that all diabetic induction models had significantly elevated blood glucose levels compared to the control group. Additionally, there were significantly differences (P0.05) in liver and kidney tissue damage among the groups treated with streptozotocin (STZ), alloxan, and STZnicotinamide. In conclusion, STZ induction produced more consistent hyperglycemia with less tissue damage compared to alloxan, while, nicotinamide co-administration effectively reduced cellular degeneration, suggesting its protective role against diabetes-induced tissue injury.